Entre la thérapie et le péché : enquêtes parallèles sur l’expression de la joie (Bernart de Ventadorn et le Roman d’Énéas) - Valeria Russo (Revue des Langues Romanes)
At the beginning of vernacular literatures in medieval Europe, courtly love in gallo-roman traditions appears as fixed within a discursive system in which the expression of joy is one of the main vectors. In the Oc and Oïl traditions, however, it appears in forms that can only be assimilated in the collective projection of the gaudium, while the manifestation of an intimate “happiness” acquires completely divergent meanings and adopts completely different contexts.